2002
DOI: 10.1146/annurev.phyto.40.030402.110010
|View full text |Cite
|
Sign up to set email alerts
|

MICROBIALPOPULATIONSRESPONSIBLE FORSPECIFICSOILSUPPRESSIVENESS TOPLANTPATHOGENS

Abstract: Agricultural soils suppressive to soilborne plant pathogens occur worldwide, and for several of these soils the biological basis of suppressiveness has been described. Two classical types of suppressiveness are known. General suppression owes its activity to the total microbial biomass in soil and is not transferable between soils. Specific suppression owes its activity to the effects of individual or select groups of microorganisms and is transferable. The microbial basis of specific suppression to four disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
961
3
33

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,488 publications
(1,062 citation statements)
references
References 207 publications
(275 reference statements)
19
961
3
33
Order By: Relevance
“…Moreover, the type of bacterial consortia and the AMF presence explained, respectively, 38.0 and 33.8% of the variance in the plant data, which means that the plant response was affected approximately equally by these two factors. Finally, even though the PGPR strains R62 and R81 produce the antibiotic 2.4-diacetylphloroglucinol (2.4-DAPG), which is known for its antifungal properties (Weller et al, 2002), the AMF growth was not affected. Indeed, the AMF root colonization percentage was similar for the control and PGPR treated plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the type of bacterial consortia and the AMF presence explained, respectively, 38.0 and 33.8% of the variance in the plant data, which means that the plant response was affected approximately equally by these two factors. Finally, even though the PGPR strains R62 and R81 produce the antibiotic 2.4-diacetylphloroglucinol (2.4-DAPG), which is known for its antifungal properties (Weller et al, 2002), the AMF growth was not affected. Indeed, the AMF root colonization percentage was similar for the control and PGPR treated plants.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities in the soil or rhizosphere contribute to plant growth by recycling nutrients and making them available (Lynch, 1990), increasing root health through competition with root pathogens (Weller et al, 2002) or enhancing nutrient uptake (Smith and Read, 1997). Wheat transfers about 30% of carbon assimilates into the soil through the process of rhizodeposition and part of this below-ground translocated C is incorporated by rhizosphere micro-organisms (Kuzyakov and Domanski, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Entre las posibles causas de las diferencias encontradas podemos señalar por un lado, y asociada con el pH del sustrato, la disponibilidad de Cu, Fe, P o Mg que son importantes para el crecimiento, la esporulación y la virulencia de F. oxysporum (Jones et al, 1993). Y por otro lado, las poblaciones de actinomicetes y otra microbiota, que se ven favorecidas con pH altos y otros factores abióticos como el origen y naturaleza del sustrato (Jones et al, 1993;Alabouvette et al, 1996), sin olvidar factores bióticos como el tipo de flora microbiana que pueda establecerse en un sustrato determinado (Weller et al, 2002).…”
Section: Análisis Morfológicosunclassified
“…Thus colonization of the imbibing seed may predispose future colonization of the root. Previous studies have shown that the fluorescent pseudomonads are aggressive colonizers of the rhizosphere of various crop plants (Weller et al, 2002;Bhattacharyya and Jha, 2012).…”
Section: Bacterial Root Colonizationmentioning
confidence: 99%